How to foster “Refuges” of biodiversity in cities, using low cost strategies - Smith, Welber Senteio; Castellari, Rafael Ramos; Sanches, Mirna Aparecida (Revista Hipótese, 2016)
Given the need to promote public policies for conservation and recovery of urban biodiversity, Sorocaba City Hall prepared the program "Sorocaba, the City Biodiversity", supporting conservation actions. Among the projects that comprise the program is the "Refuges Biodiversity" which aims to qualify areas in the city as PPAs, parks, plazas, lakes, streams and the Sorocaba River to conserve flora and fauna. They were established 29 areas of "Refuges Biodiversity", marked by educational boards and the planting of 12,500 native seedlings. The educational work sensitize the population to the implementation of refuges and involved the press, actions in schools and municipal parks.